Perancangan Sistem Prediksi Minat Mata Pelajaran Siswa di Sekolah SDT Muhammadiyah Dengan Metode Algoritma Naive Bayes - Asyadila; David JM Sembiring; Sri Novida Sari (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
The design of a student subject interest prediction system at SDT Muhammadiyah School is crucial to help the school understand and enhance the quality of education. This system is developed using the Naive Bayes algorithm method, which is known to be effective in analyzing historical data to predict students' preferences for specific subjects. With this system, the school can identify the subjects most favored by students, enabling the development of more targeted and interest-aligned learning strategies. Based on this issue, the author designed a student subject interest prediction system at SDT Muhammadiyah School using the Naive Bayes algorithm method.